ANALYSIS AND REVIEW OF THE POSSIBILITIES OF APPLICATION OF SATELLITE COMMUNICATIONS IN 5G NETWORKS - R.R.Ibraimov; D.A.Davronbekov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The main technical requirements for 5G networks are given, the integration of satellite systems with the terrestrial infrastructure of 5G mobile operators is discussed. The statements of experts from the world’s leading companies involved in the development of 5G networks are given and a summary is provided on this issue.